2018
DOI: 10.1021/jacs.8b06930
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity Enhancement of a Zerovalent Diboron Compound by Desymmetrization

Abstract: The desymmetrization of the cyclic (alkyl)(amino)carbene-supported diboracumulene B(cAAC) (cAAC = 1-(2,6-diisopropylphenyl)-3,3,5,5-tetramethylpyrrolidin-2-ylidene) by monoadduct formation with IMe (1,3-dimethylimidazol-2-ylidene) yields the zerovalent sp-sp diboron compound B(cAAC)(IMe), which provides a versatile platform for the synthesis of novel symmetrical and unsymmetrical zerovalent sp-sp diboron compounds by adduct formation with IMe and CO, respectively. Furthermore, B(cAAC)(IMe) displays enhanced re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 47 publications
(52 reference statements)
1
23
0
6
Order By: Relevance
“…Unsymmetrically-substituted diboron compounds are known to display higher reactivity than their symmetrical counterparts. 39,40 We have previously shown that unsymmetrical diborenes 2 and 3 (Scheme 2) react more quickly than 1 in diboration reactions with B 2 cat 2 . 33 Treatment of compound 2 with HPPh 2 resulted in complete conversion to a new compound within 3 h at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Unsymmetrically-substituted diboron compounds are known to display higher reactivity than their symmetrical counterparts. 39,40 We have previously shown that unsymmetrical diborenes 2 and 3 (Scheme 2) react more quickly than 1 in diboration reactions with B 2 cat 2 . 33 Treatment of compound 2 with HPPh 2 resulted in complete conversion to a new compound within 3 h at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…While 18 reacts selectively with one equivalent of dihydrogen, 209 it was also found that its coordination to one equivalent of Me IMe (1,3,4,5-tetramethylimidazol-2-ylidene) -which breaks the symmetry of the diboracumulene to give complex 23 -increases its reactivity (Figure 15). In this bound state, 23 reacts rapidly with two equivalents of molecular hydrogen in a process that completely cleaves the B-B bond.…”
Section: Metallomimetic Chemistry Of B-b Bondsmentioning
confidence: 99%
“…15 As for 10, its sp-hybridized boron atom exhibits enhanced nucleophilicity with respect to its symmetrical precursor; consequently, intramolecular C-H bond activation and H 2 addition involving B=B double-bond activation and cleavage, respectively, occurred. 16…”
Section: Diboron Reagentsmentioning
confidence: 99%